Intestinomesenteric infarction: Diagnosis and treatment - Praderi, Luis A (Cirugía del Uruguay, 1972)
Diagnostica! and therapeutic problems are discussed since a better knowledge may aid in reducing the high deathrate of this disease. Its diagnosis is difficult (38 % ) and is based on a high suspicion rate; its early stages require treatment. There are two stages in its clinical course and its symptomatology has 4 ethiopathogenic groups: embolism, A. thrombosis, V thrombosis and non-occlusive disease. Its therapy, medico-surgical problems and drugs employed are discussed. Methodology far surgical exploration on its intestinal and vascular focus, is established, as well as resources and procedures of direct vascular surgery and risks of abrupt restoration of flow. The advantages of an early second look are discussed. The paper also contains a review of results and survival rate in national and foreign statistics.